Interference With the Work of Dog Guides in Public: A Survey. (September 2022) - Allman, Melissa R.; Freeberg, Kathleen; Evans, Katy M.
Introduction: One of the greatest challenges dog guide handlers face after completing training is interference with their dogs' work, both from people and other dogs. The Seeing Eye surveyed its active dog guide handlers to gain a better understanding of the types and severity of interference they were currently experiencing and to develop strategies to better equip handlers to deal with that interference.Methods: For one month (October 2019), an online survey was made available to the 1, 761 active Seeing Eye handlers concerning the interference they had experienced while working their dogs in public within the past 5 years. The survey questions were designed to elicit information about the types, frequency, and severity of interference handlers experience both from people and other dogs, as well as the settings in which the interference took place. Descriptive statistics were used to analyze the data.Results: Eighty-nine percent of handlers had experienced people interfering with the work of their dogs at least occasionally by talking to or making eye contact with them, and 78% had experienced interference from other dogs regularly. Interference from other dogs was usually nonaggressive, but 36% reported other dogs making aggressive physical contact with their dogs. Interference of all types mostly occurred in public places.Discussion: A robust, multifaceted public awareness campaign is necessary to address the persistent problem of interference with dog guide teams.Implications for Practitioners: Many factors influence a person's decision about whether to work with a dog guide. This study provides practitioners with a more realistic picture of the challenges handlers are likely to face in their encounters with the public. Practitioners and dog guide schools can use the information in the study to better equip and support dog guide handlers to proactively engage the public and manage interference when it does occur.